2014
DOI: 10.1021/om500518r
|View full text |Cite
|
Sign up to set email alerts
|

Iron Phosphine Catalyzed Cross-Coupling of Tetraorganoborates and Related Group 13 Nucleophiles with Alkyl Halides

Abstract: Iron phosphine complexes prove to be good precatalysts for the cross-coupling of alkyl, benzyl, and allyl halides with not only aryl triorganoborate salts but also related aluminum-, gallium-, indium-, and thallium-based nucleophiles. Mechanistic studies revealed that while Fe(I) can be accessed on catalytically relevant time scales, lower average oxidation states are not formed fast enough to be relevant to catalysis. EPR spectroscopic studies reveal the presence of bis(diphosphine)iron(I) complexes in repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 147 publications
5
43
0
1
Order By: Relevance
“…[151] It was later experimentally shown that an iron(I) complex is ac ompetent catalyst for such cross-couplings. [152] Based on computational studies,t he groups of Gutierrez [153] and Nakamura and Morokuma [154] independently proposed two slightly different mechanisms for such iron cross-couplings.It was suggested in both cases that an iron(I) species first reductively cleaves the alkyl halide (Figure 31 b, step A) to give an iron(II) intermediate and aC radical. TheF e II complex is able to trap the transient alkyl radical (step C) to generate an iron(III) complex, which then undergoes reductive elimination (step D) to liberate the coupling product, thereby regenerating the starting iron(I) species.…”
Section: Ironmentioning
confidence: 99%
“…[151] It was later experimentally shown that an iron(I) complex is ac ompetent catalyst for such cross-couplings. [152] Based on computational studies,t he groups of Gutierrez [153] and Nakamura and Morokuma [154] independently proposed two slightly different mechanisms for such iron cross-couplings.It was suggested in both cases that an iron(I) species first reductively cleaves the alkyl halide (Figure 31 b, step A) to give an iron(II) intermediate and aC radical. TheF e II complex is able to trap the transient alkyl radical (step C) to generate an iron(III) complex, which then undergoes reductive elimination (step D) to liberate the coupling product, thereby regenerating the starting iron(I) species.…”
Section: Ironmentioning
confidence: 99%
“…Carbon-carbon bonds through iron catalysis are mainly formed either through coupling of a nucleophile with an electrophile (Scheme 2) or through cross dehydrogenative coupling (CDC, Scheme 3). The general pattern of coupling a nucleophile with an electrophile is shown in Scheme 2 together with some notable iron-catalyzed examples [40][41][42]. This chemistry will be described further by Robin Bedford in [29].…”
Section: C-c Bond-forming Reactionsmentioning
confidence: 99%
“…2 Bedford et al 3 and Nakamura et al 4 have reported Fe-diphos catalysed Negishi couplings and recently Fe-monophos catalysed Negishi couplings. 6 The mechanisms of Fe-catalysed cross-coupling reactions have been the subject of much discussion and an explanation of the ligand effects has yet to emerge. 6 The mechanisms of Fe-catalysed cross-coupling reactions have been the subject of much discussion and an explanation of the ligand effects has yet to emerge.…”
mentioning
confidence: 99%